The small GTPase Rap1 in POMC neurons regulates leptin actions and glucose metabolism - Kentaro Kaneko; Weisheng Lu; Yong Xu; Alexei Morozov; Makoto Fukuda (Molecular Metabolism)
The hypothalamic leptin-proopiomelanocortin (POMC) pathway is critical for regulating metabolism. POMC neurons in the arcuate nucleus respond to leptin and play a pivotal role in mediating energy and glucose balance. However, during diet-induced obesity (DIO), these neurons often develop resistance to exogenous leptin. Recently, the small GTPase Rap1 has been implicated as an inhibitor of neuronal leptin signaling; however, its specific role within POMC neurons remains unexplored. We generated tamoxifen-inducible, POMC neuron-specific Rap1 knockout mice to selectively delete both Rap1a and Rap1b isoforms in POMC neurons. By analyzing these mice through metabolic phenotyping, immunohistochemistry, and biochemical assays, we show that deleting Rap1a and Rap1b in POMC neurons prior to exposing the mice to a high-fat diet significantly prevented weight gain compared to control mice. Furthermore, while DIO mice with intact Rap1 failed to respond to exogenous leptin, genetically removing the Rap1 genes from DIO mice enhanced the ability of exogenous leptin to induce anorectic effects. Remarkably, acute deletion of Rap1 in POMC neurons of already obese mice improved hyperglycemia within one week, with minimal effect on body weight. This glycemic improvement was accompanied by improved glucose tolerance, enhanced insulin sensitivity, and improved cellular insulin signaling. Collectively, these findings suggest that loss of Rap1 in POMC neurons enhances leptin sensitivity, acutely improves glucose balance, and may offer a potential strategy to lower hyperglycemia in dietary obesity.